Efforts in Increasing Physics Learning Outcomes: Comparing Two Different Methods - Fitriani Kadir; Imam Permana (Universitas Muhammadiyah Makassar, 2022)
The teaching method used by the teacher is closely related to the results obtained by students during learning. This study aims to analyze whether there are differences in students' learning outcomes of physics taught by problem-solving and probing prompting methods and which method is more effective in improving physics learning outcomes. This type of research is experimental, with a post-test only control group design. The population in this study were all students of class X MAN 2 Model Makassar, which consisted of six classes with a total of 252 students, while the sample was taken using a random class technique. Class X MIA 2 and class X MIA 3 were selected as samples, with a total of 42 students in each class. The results showed that in the cognitive domain, the physics learning outcomes average score of students who were taught using the problem-solving method was 77.08; meanwhile, that of the students taught by the probing prompting method was 81.00. In the psychomotor domain, the learning outcomes average score obtained by the class taught by problem-solving method and probing prompting method were almost equal, that was 98.32 and 98.28, respectively. Finally, in the affective domain, the students’ learning outcomes after using the problem-solving method was 84.20, and that after using the probing prompting method was 83.90. Therefore, it can be concluded that there are differences in physics learning outcomes between students who are taught using problem-solving and probing prompting methods. The probing prompting method is more effective in increasing students’ learning outcomes in the cognitive domain, while the problem-solving method is more effective in developing students’ psychomotor and affective domains.